2018
DOI: 10.1371/journal.pone.0202881
|View full text |Cite
|
Sign up to set email alerts
|

Physiological analysis of the effect of altitudinal gradients on Leymus secalinus on the Qinghai-Tibetan Plateau

Abstract: On the Qinghai-Tibetan Plateau, the high-altitudinal gradients can negatively affect plant distribution and limit plant growth and reproduction. Leymus secalinus (Georgi) Tzvel. is an important forage crop on the Qinghai-Tibetan Plateau and has an excellent ability to fix sand and improve soil. To evaluate the effect of altitude on the physiological characteristics of L. secalinus on the Qinghai-Tibetan Plateau, we measured the lipid peroxidation; chlorophyll a (Chl a), chlorophyll b (Chl b), total carotenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…Negative influence of altitude gradient was also shown on the growth and synthesis of some metabolites (photosynthetic pigments, malondialdehyde, etc.) in Leymus secalinus, assessed across eight different altitudes in the Qinghai-Tibetan Plateau [41]. However, these authors observed that proline, soluble sugar contents and other markers of stress increased with elevation.…”
Section: Discussionmentioning
confidence: 93%
“…Negative influence of altitude gradient was also shown on the growth and synthesis of some metabolites (photosynthetic pigments, malondialdehyde, etc.) in Leymus secalinus, assessed across eight different altitudes in the Qinghai-Tibetan Plateau [41]. However, these authors observed that proline, soluble sugar contents and other markers of stress increased with elevation.…”
Section: Discussionmentioning
confidence: 93%
“…Possibly the most obvious difference between geographical location would be the altitude of each field: UK celery was grown on an east-facing field that was −1 to 1 m above sea level, whereas the field in Aguilas was south-facing at 390 m above sea level. Higher altitudes will result in lower temperatures and limitations on light exposure [ 61 ]. Cui et al [ 61 ] investigated the physiological changes of Leymus secalinus and the effect of altitude, observing an increase in soluble sugars as elevation increased but a decrease in chlorophyll a and b , leading to a decrease in the crop’s ability to absorb light.…”
Section: Resultsmentioning
confidence: 99%
“…Higher altitudes will result in lower temperatures and limitations on light exposure [ 61 ]. Cui et al [ 61 ] investigated the physiological changes of Leymus secalinus and the effect of altitude, observing an increase in soluble sugars as elevation increased but a decrease in chlorophyll a and b , leading to a decrease in the crop’s ability to absorb light. Both these reactions were noted as defence mechanisms and adaption strategies to the change in environment.…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation strategies to the elevation can be triggered in the plants as a result of combined effects of multiple environmental factors such as increase in UV radiation, increase in the atmospheric pressure, decrease in the temperatures, alteration in precipitation, alteration in CO 2 and O 2 concentrations with elevation [54]. Herbs that have a cushion-like habit, such as representative of the Saxifragaceae family, can also be significant to local species richness.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have developed various adaptation strategies to overcome the environmental stress and to survive in extreme environmental conditions at high altitudes, such as synthesis of photoprotective compounds [16], activation of the plants' antioxidant defense system, stress related hormones, osmotic adjustment, morphological alterations in some structures, etc. [17,19,48,[51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%